EMERGING EDUCATIONAL INNOVATIONS FOR TRANSFORMING TEACHING AND LEARNING OF ADULT AND NON-FORMAL EDUCATION DURING COVID-19 PANDEMIC AND BEYOND - OLAJIDE, MUILI FOLARANMI; WUSHISHI, ABDU IDRIS; OLAJIDE, FATAHAT OYETEJU (Sokoto Educational Review, 2023)
This paper is focused on emerging educational innovations for transforming teaching and learning of adult and nonformal education during COVID-19 pandemic and beyond. The objective of this paper is to examines the positive impulse of adopting adult and non-formal education emerging innovations for teaching and learning which are all encompassing in ensuring no educational gap is created among the adult learners during the pandemic and beyond. The objective further premised on adult and non-formal education as an education with the capability of using digital knowledge as innovations to impact on adult learners during the pandemic and beyond. This will transform teaching and learning components of the adult education and guaranteed continuous learning for the learners. The paper however discussed, concept of adult and nonformal education, concept of innovation in transforming teaching and learning in adult education, emerging educational innovations opportunities for teaching and learning, pedagogy for adult and non-formal education learners during the pandemic and beyond, emerging educational innovations for teaching and learning of adult and nonformal education and challenges of emerging educational innovations for transforming adult and nonformal education teaching and learning. The paper concluded that to achieve the emerging educational innovations for teaching and learning during the pandemic and beyond, adult and non-formal education is the education system to embrace with the nexus to deliver on inclusive education. The paper suggested among others, that government should incorporate digital information in adult and non-formal education system, so as to achieve meaningful teaching and learning during pandemic and beyond.